2019
DOI: 10.1111/tbj.13298
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective statistical analysis on the diagnostic value of ductography based on lesion pathology in patients presenting with nipple discharge

Abstract: Purpose To compare sensitivities and specificities of ductography to noninvasive imaging studies in determining the cause of nipple discharge and assess the value of ductography on the basis of pathologic results. Methods In this retrospective review of women with nipple discharge who underwent ductography between January 1, 2005 and October 30, 2015, at our institution, we compared ductography with noninvasive imaging results (mammography, ultrasound, MRI) to determine its relative diagnostic sensitivity, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…In contrast, some authors consider DG to be the gold standard and are confident that its high (up to 95.0%) sensitivity allows identification of IDP and providing supporting evidence for surgical intervention (4,5). According to the criteria of the American College of Radiology (ACR), DG is not a mandatory procedure, but DG may be used by surgeons who need additional information about the topography of IDP (6).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some authors consider DG to be the gold standard and are confident that its high (up to 95.0%) sensitivity allows identification of IDP and providing supporting evidence for surgical intervention (4,5). According to the criteria of the American College of Radiology (ACR), DG is not a mandatory procedure, but DG may be used by surgeons who need additional information about the topography of IDP (6).…”
Section: Introductionmentioning
confidence: 99%
“…The most common causes of PND are benign conditions, such as papilloma or duct ectasia, although it indicates underlying malignancy in 5%–23% of the cases [ 1 2 3 ]. Although various diagnostic tools have been employed, it remains controversial whether mammography, ductography, ultrasound (US), or specific combinations of multiple modalities represent the optimal radiological examination approach [ 4 5 ]. For men or women with PND, aged ≥ 40 years, diagnostic mammography, digital breast tomosynthesis, and US at the initial examination are recommended by the American College of Radiology (ACR) and National Comprehensive Cancer Network (NCCN) [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between US and ductography have revealed inconsistent results [ 9 13 20 21 ]. Nevertheless, several studies have reported that a combination of US and ductography facilitates lesion localization and characterization [ 5 10 22 23 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional galactography is a scanning two-dimensional (2D) full-field digital mammography (FFDM) [7,10,11]. It may be affected by the lesion-masking effect of overlapping normal tissue and produce false-negatives or false-positive findings.…”
Section: Introductionmentioning
confidence: 99%